A Study On Hospital Disaster Preparedness: A Case Study Of Selected Hospitals Based On The 2014 Flood In Kelantan, Malaysia - Zamree, Norsyazana Ahmad (2021)
Floods are one of the common natural disasters occurred in most part of the world. In December 2014, the east coast of Peninsular Malaysia was hit by the massive flood ever recorded in history especially Kelantan. The 2014 flood was affected by several hospitals in Kelantan that left hospitals unable to provide services to patients. This has led to the realization of hospital disaster preparedness and management was important to be closely monitored and addressed. This research presents a case study that investigates the hospital disaster preparedness level of selected hospitals affected by the 2014 flood in Kelantan. This research used a qualitative study and guided interviews with hospital disaster committee members were carried out. The results show that the hospital has a disaster action plan to use as a complete guide to the elements of prevention, preparedness, response, and recovery. However, the hospital was not aware that the action plan is a disaster preparedness model that needs to be streamlined for all hospital staff to practice. This research suggested for hospitals to adopt an existing hospital disaster action plan using Disaster Risk Management- Sustainable Development by Centre for Global Sustainability Study, Universiti Sains Malaysia which is a complete framework for disaster preparedness model.